Business models for peer-to-peer energy trading in Germany based on households' beliefs and preferences. (15th January 2022) - Karami, Mahdi; Madlener, Reinhard
Abstract: With the expansion of distributed energy resources and the phaseout of the feed-in-tariff scheme in Germany, self-consumption and electricity sharing within a community of prosumers are becoming more profitable. This paper derives optimal business models for a sustainable peer-to-peer (P2P) energy trading platform (ETP) in Germany. It examines data from 1618 residential households collected from an online survey, including 1311 consumers and 307 prosumers. Our research aims to better understand under what circumstances these households would participate in a P2P ETP and how business models can support such platforms to create added value for private households. Therefore, households' beliefs concerning their attitudes, perceived behavioral control, and subjective norms are analyzed according to the Theory of Planned Behavior, and business models are designed correspondingly. In order to evaluate the developed business models' effectiveness and usefulness, we apply them to fifteen existing pioneer energy communities and platforms in Germany. We find that cost-saving and other financial benefits for households must be considered to be the primary value proposition offered by a service provider. Business models which help households to become more electricity self-sufficient and to consume less electricity from the public grid are the second-most important source of value creation from a household's point of view. By connecting the business models and the P2P prosuming market model, recommendations for companies, policy-makers, and regulatory authorities are made. Highlights: Households decide to become prosumers due to cost savings and financial benefits. A suite of business models for future energy service providers is suggested. Business models increase households' financial benefits and save on energy costs. Business models proposed enable households to increase energy self-sufficiency. Companies should focus more on creating P2P energy-sharing communities or platforms.